Education on Scientific Literacy and Pandhalungan Culture through Arduino-Based 3D Up Book Learning Media for Deaf Children at SLBN Jember - Diana Kamalia; Ega Bonansyah Utoyo; Amar Ma’ruf Al Bawani; Jalis Syarifah; Muhamad Taufiqurrohman; Lailatul Nuraini (PT Inovasi Pratama Internasional, 2023)
Learning media can help improve the quality of education. However, the limitations of learning media can cause problems in learning. The availability of learning media is also needed for children with special needs such as deaf children. The development of increasingly sophisticated technology can be utilized to create science and technology-based learning media. One of them uses the arduino-based 3D Up Book learning media for deaf children. In addition, it contains Pandhalungan culture as a way to introduce culture to students. This community service activity aims to determine the effectiveness of the arduino-based 3D Up Book learning media for deaf children and describe the responses of teachers and students to the PKM-PM program at SLBN Jember. The community service method used is Asset Based Community Development (ABCD) by utilizing the potential of the local community. The results of community service show that 3D Up Book media is effectively used in learning and gets a very interesting response from teachers and students.